HLA-DRB3/4/5 Matching Improves Outcome of Unrelated Hematopoietic Stem Cell Transplantation - Tsamadou, Chrysanthi; Engelhardt, Daphne; Platzbecker, Uwe; Sala, Elisa; Valerius, Thomas; Wagner-Drouet, Eva; Wulf, Gerald; Kröger, Nicolaus; Murawski, Niels; Einsele, Hermann; Schaefer-Eckart, Kerstin; Freitag, Sebastian; et al. (Frontiers in Immunology, 2021)
The HLA-DRB3/4/5 loci are closely linked to the HLA-DRB1 gene. Mismatches in these loci occur with a frequency of about 8%–12% in otherwise 10/10 HLA-matched transplant pairs. There is preliminary evidence that these disparities may associate with increased acute graft-versus-host disease (GvHD) rates. The aim of this study was to analyze a large cohort of German patients and their donors for HLA-DRB3/4/5 compatibility and to correlate the HLA-DRB3/4/5 matching status with the outcome of unrelated hematopoietic stem cell transplantation (uHSCT). To this end, 3,410 patients and their respective donors were HLA-DRB3/4/5 and HLA-DPB1 typed by amplicon-based next-generation sequencing (NGS). All patients included received their first allogeneic transplant for malignant hematologic diseases between 2000 and 2014. Mismatches in the antigen recognition domain (ARD) of HLA-DRB3/4/5 genes were correlated with clinical outcome. HLA-DRB3/4/5 incompatibility was seen in 12.5% (n = 296) and 17.8% (n = 185) of the 10/10 and 9/10 HLA-matched cases, respectively. HLA-DRB3/4/5 mismatches in the ARD associated with a worse overall survival (OS), as shown in univariate (5-year OS: 46.1% vs. 39.8%, log-rank p = 0.038) and multivariate analyses [hazard ratio (HR) 1.25, 95% CI 1.02–1.54, p = 0.034] in the otherwise 10/10 HLA-matched subgroup. The worse outcome was mainly driven by a significantly higher non-relapse mortality (HR 1.35, 95% CI 1.05–1.73, p = 0.017). In the 9/10 HLA-matched cases, the effect was not statistically significant. Our study results suggest that mismatches within the ARD of HLA-DRB3/4/5 genes significantly impact the outcome of otherwise fully matched uHSCT and support their consideration upon donor selection in the future.